2014
DOI: 10.1094/phyto-07-13-0191-r
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Trehalose Induces Defenses in Wheat Before and During a Biotic Stress Caused by Powdery Mildew

Abstract: Powdery mildew would be one of the most damaging wheat diseases without the extensive use of conventional fungicides. Some of the alternative control strategies currently emerging are based on the use of resistance inducers. The disacharride trehalose (TR) is classically described as an inducer of defenses in plants to abiotic stress. In this work, the elicitor or priming effect of TR was investigated in wheat both before and during a compatible wheat-powdery mildew interaction through molecular, biochemical, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 60 publications
1
40
0
2
Order By: Relevance
“…Trehalose is a disaccharide, which is found in the majority of plants in only trace amounts and has been thought to control basic plant processes as well as being involved in resistance to abiotic stress factors and signalling. More recent work is now showing that it is trehalose‐6‐phosphate, a precursor of trehalose, which is the signalling molecule (Paul et al , 2008; O'Hara et al , 2013) and interestingly it has been shown that treating wheat with trehalose can induce partial protection against the powdery mildew pathogen ( Blumeria graminis ), which could be because of the activation of defence responses (Reignault et al , 2001; Tayeh et al , 2014). Trehalose is important to insects, as the starting point in chitin synthesis (Paul et al , 2008) and is known to occur in the haemolymph of the aphids Megoura viciae and Acyrthosiphon pisum (Rhodes et al , 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Trehalose is a disaccharide, which is found in the majority of plants in only trace amounts and has been thought to control basic plant processes as well as being involved in resistance to abiotic stress factors and signalling. More recent work is now showing that it is trehalose‐6‐phosphate, a precursor of trehalose, which is the signalling molecule (Paul et al , 2008; O'Hara et al , 2013) and interestingly it has been shown that treating wheat with trehalose can induce partial protection against the powdery mildew pathogen ( Blumeria graminis ), which could be because of the activation of defence responses (Reignault et al , 2001; Tayeh et al , 2014). Trehalose is important to insects, as the starting point in chitin synthesis (Paul et al , 2008) and is known to occur in the haemolymph of the aphids Megoura viciae and Acyrthosiphon pisum (Rhodes et al , 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of studies reports are available in the literature which show a significant effect of trehalose on abiotic stress tolerance in different crops (Iordachescu and Imai 2008;Ali and Ashraf 2011;Li et al 2011;Ali et al 2012), a little information is found regarding the effect of trehalose on membrane permeability/leakage except that of Tayeh et al (2014) on wheat plants in which they observed that exogenously applied trehalose improved lipid metabolism due to upregulation of lipoxygenase and lipid-transfer protein under stress conditions. In radish plants, reduced accumulation of essentially required mineral nutrients for optimum growth such as K ?…”
Section: Discussionmentioning
confidence: 99%
“…and Xanthomonas citri subsp. citri (Freeman et al, 2010;Djonovi c et al, 2013;Piazza et al, 2015), but is a double-edged sword for the pathogens as it is also a trigger for defense responses by the host plant (Reignault et al, 2001;Renard-Merlier et al, 2007;Tayeh et al, 2014;Piazza et al, 2015). Trehalose is also implicated as a signal molecule during formation of rhizobial and mycorrhizal symbioses (Fig.…”
Section: Tre6p and Abiotic Stress Tolerancementioning
confidence: 99%